The barrier techniques for airway management in covid-19 patients - review of literature - Pratishtha Yadav; Rakesh Garg (Wolters Kluwer Medknow Publications, 2021)
The coronavirus disease 2019 (COVID-19) has emerged as a pandemic and shall prevail for some time around the globe. The disease can manifest from asymptomatic to severe respiratory compromise requiring airway intervention. Transmission of COVID-19 has been reported to be by droplets, fomites, and aerosols, and airway management is an aerosol-generating procedure. The high viral load in the patient's airway puts the clinician performing intubation at a very high risk of viral load exposure. So, the need for barrier devices was considered and led to reporting of various such devices. All these devices have been reported individually and have not been compared. We present a review of all the information on these devices based on the reported literature.